Venganza, realización de la libertad y guerra privada - Padial, Juan J. (THÉMATA. Revista de Filosofía, 2013)
Este artículo estudia la venganza en Hegel, como una forma prejurídica de regulación de la violencia impregnada de religiosidad, y que se realiza según un ritual. En este sentido Hegel anticipa las consideraciones de Max Weber y Emil Durkheim sobre la venganza. This paper studies revenge according to Hegel. Revenge is a primitive, pre-juridical form of violence regulation. As proper of primitive societies, revenge or blood feud is pervaded of religiosity, and it is carried out according to certain rituals. In this sense, Hegel anticipates the considerations of Max Weber and Emil Durkheim on blood feud, which has been researched by Jonas Grutzpalk.